The role of epitaxial strain on the spontaneous formation of Bi-rich nanostructures in Ga(As,Bi) epilayers and quantum wells - Luna, Esperanza; Puustinen, Janne; Wu, Mingjian; Hilska, Joonas; Guina, Mircea; Trampert, Achim (Nanoscience and Nanotechnology Letters, 2017)
In this work, we explore the role of epitaxial strain on the spontaneous development of Bi-richnano-structures within Ga(As, Bi) epilayers and Ga(As, Bi)/GaAs quantum wells (QWs) grown by molecular beam epitaxy. We observe the spontaneous formation of ordered arrays of uniform nanometer-sized Bi-rich structures in Ga(As, Bi)/GaAs QWs and of columnar-like Bi-rich regions in Ga(As, Bi) epilayers, respectively. A correlation between the microstructure and the growth conditions is established. In particular, we find that the As/Ga flux ratio has a significant impact and that epilayers grown at high temperature (315 degrees C) are homogeneous. The formation mechanism of such microstructure is discussed in terms of the epitaxial strain effect versus the composition effect (i.e., the phase separation tendency of the alloy). We demonstrate that the accumulation of epitaxial strain due to the lattice mismatch can not explain our experimental observations. On the other hand, we find that the spontaneous formation of the nanostructures is the consequence of a surface-directed decomposition process at the growing front due to the inherent tendency of the alloy to phase separate. Surface processes (including Bi surface segregation) are decisive in determining the final morphology.
Keywords: Dilute Bismides; Phase Separation; Transmission Electron Microscopy; Semiconducting III-V Materials